PENGEMBANGAN KOMODITAS TANAMAN PANGAN POKOK SEHUBUNGAN DENGAN PERKEMBANGAN PERMUKIMAN KAWASAN IBUKOTA KABUPATEN KUPANG - Elton R. M. Djala; Ida Nurwiana; Fidelis Klau (Buletin Ilmiah Impas, 2021)
This research has been conducted in East Kupang District, Kupang Regency with the aim of knowing the superior staple food crop commodities and analyzing the zone dynamics of staple food crops as a result of changes in residential areas (housing and infrastructure) in 2013 and 2018 using the Geographical Information System (GIS). . The results showed that rice and green beans were the main staple crops in East Kupang District with an average LQ coefficient of 2.36 for rice and 1.29 for green beans, assuming there was no change in technology. The dynamics of the land zone for staple food crop commodities in East Kupang Subdistrict in the period 2013 and 2018, showed changes in residential land use covering an area of ​​1,104.37 hectares or the growth rate for settlements increased by 0.084% while the rate of decline in agricultural land for staple food crops was 0.0095% which means the rate of settlement increase is faster than the rate of decline in agricultural land for staple food crops.